Cultivating an Attitude of Religious Moderation for Students at SD Eppata II Batu Aji Batam - Rita Evimalinda; Rikardo Dayanto Butar-Butar; Evans Dusep Dongoran; Hanyta Priscila Harahap; Viktor Deni Siregar; Yunira Nababan; Nia Lorena Hutagalung; Selvinus Yohame; Devina Romauli Nadapdap; Kristina Natalia Siregar; Rasmita Br. Sitepu; Ester Br. Simbolon; Suzaya Bitia Silsilia; Vera Angelyna Pakpahan (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Abstract: Religious moderation is a manner of view, attitude, and behavior that always takes a position in the middle, is always fair, and is diligent in religion. Generalities also emphasize the importance of tolerance and respect for one another's religious differences and differing views. Religious moderation is a multicultural road that entices all religions in Indonesia by upholding the values, tolerance, and harmony between religions. This is to enable all believers to honor one another and understand sesame. Religious moderation also focuses on increased mutual compassion, equality, and understanding among religious people. The PKM team (devotion to society) conducted a study with the eppata ii stone aji batam elementary, with the program for the implanting of religious imposition for students. This PKM activity is done to help learners in the use of the Christian language and values and to improve the quality of the learning process. The result of this activity is that students can understand how to respect one another, tolerate one another, and understand how to act politely toward others. Keyword: Moderation, Religion, And Learne Abstrak Moderasi beragama merupakan cara pandang, sikap, dan perilaku yang selalu mengambil posisi di tengah-tengah, selalu bertindak adil, dan tekun dalam beragama. Moderasi beragma juga menekankan pentingnya toleransi dan saling menghargai perbedaan agama dan pandangan yang berbeda. Moderasi beragama merupakan jalan tengah multicultural Indonesia yang mengakomodir semua agama yang ada di Indonesia dengan cara menegakkan nilai-nilai luhur, toleransi, dan kerukunan antar umat beragama. Hal ini bertujuan agar semua umat beragama dapat saling menghormati dan memahami sesame. Moderasi beragama juga berfokus pada peningkatan rasa saling kasih sayang, kesetaraan, dan pemahaman antar umat beragama. Tim PKM (Pengabdian Kepada Masyarakat) melakukan suatu penelitian ke SD Eppata II Batu Aji Batam, dengan program penanaman sikap moderasi beragama bagi pelajar. Kegiatan PKM ini dilakukan untuk membantu peserta didik dalam penggunaan berbahasa dan nilai-nilai kekristenan dan meningkatkan kualitas proses pembelajaran. Hasil yang diperoleh dari kegiatan ini adalah pelajara dapat memahami bagaimana caranya saling menghormati, saling bertoleransi satu dengan yang lain, dan memahami bagaimana cara bertata kerama yang sopan terhadap orang lain. Kata Kunci: Moderasi, Agama, dan Peserta didik